Public Sector Financial Management to Realize Good Governance at the General Election Supervisory Board of Manado City - Eman, Victor Ady; Mandagi, Marthinus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to describe, analyze and describe how the procurement of goods and services of Bawaslu Manado and the provider and to find out the factors for the occurrence of wan prestasi between Bawaslu Manado and third parties (providers). The research method uses a qualitative approach. Data collection techniques with interviews, documentation studies and observation. The results showed that the planning flow had been carried out properly based on the basic conditions of need and priority scale. The implementation system of leasing goods and services in the financial management of Bawaslu Manado City is in accordance with applicable procedures and rules, including the results of work that meet the criteria of applicable regulations and have adhered to the principles of good governance as a form of mutual commitment.